COMPARATIVE ANALYSIS OF THE PREFACE TO THE WORKS "GULISTON" BY SAADI SHERAZI AND "GULISTON BIT-TURKI" BY SAYFI SARAI - Khazratkulova Shakhsanam Sharofiddinovna; Prof. Dilnavoz Yusupova (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the introductory parts of the works of the Persian writer Saadi Shirazi “Gulistan” and its free translation “Gulistan bit-turki” are analyzed. Similarities and differences in the preface of the work and its translation are identified.